Effectiveness and acceptance of Vestibulo-Ocular Reflex adaptation training in children with recurrent vertigo with unilateral vestibular dysfunction and normal balance function - Ma, Ning; Liu, Handi; Liu, Bing; Zhang, Li; Li, Bei; Yang, Yang; Liu, Wei; Chen, Min; Shao, Jianbo; Zhang, Xiao; Ni, Xin; Zhang, Jie (Frontiers in Neurology, 2022)
Objective This was a block randomized controlled study to evaluate the effectiveness and acceptance of Vestibulo-Ocular Reflex (VOR) adaptation training in children with recurrent vertigo with unilateral vestibular dysfunction (UVD) and normal balance function. Methods Thirty children, aged 4–13 years, diagnosed with recurrent vertigo of childhood (RVC) with UVD (according to a caloric test) and normal balance function were analyzed. These 30 children were divided into 10 blocks based on similar age and severity of vertigo. Three children in each block were randomly assigned to one of three groups to receive 1 month of treatment. Group A received vestibular-ocular reflex (VOR) adaptation training, Group B received Cawthorne-Cooksey training, and a control group received no training. All children were administered pharmacotherapy [Ginkgo biloba leaf extract (drops)]. The Dizziness Handicap Inventory (DHI), Visual Analog Scale of Quality of Life with Vertigo (VAS-QLV), and canal paralysis (CP) on the caloric test were recorded before and after treatment, and the effectiveness of treatment was evaluated. The Visual Analog Scale of Acceptance (VAS-A) was used to evaluate the acceptance of the training in the two groups that received training. Results There were 10 children each in Group A, Group B, and the control group; the male to female ratio was 1, and the average age in each group was 9.0 ± 3.2, 8.4 ± 3.0, and 8.3 ± 2.6 years, respectively. The effective rate was 100% in Group A, 65% in Group B, and 60% in Group C. The recovery rate on caloric testing after treatment was 100, 70, and 50%, respectively. DHI scores before and after training were 56.8 ± 12.4 and 8.8 ± 6.1 in Group A, 57.8 ± 12.6 and 18.8 ± 9.7 in Group B, and 56.8 ± 12.4 and 24.0 ± 15.3 in Group C (all P = 0.000). VAS-QLV scores before and after training were 7.5 ± 1.0 and 0.9 ± 0.9 in Group A, 6.4 ± 2.2 and 2.7 ± 1.1 in Group B, and 6.6 ± 1.6 and 2.6 ± 1.4 in Group C (all P < 0.05). The CP values before and after training were 35.7 ± 15.1 and 12.9 ± 8.7 in Group A, 33.6 ± 20.1 and 23.6 ± 19.3 in Group B, and 38.6 ± 21.1 and 24.8 ± 17.9 in Group C (P = 0.001, P = 0.015, and P = 0.050, respectively). Between-group comparisons showed that the decreases in DHI and VAS-QLV scores after training were significantly different (P = 0.015, P = 0.02), while CP values were not (P = 0.139). After training, the DHI value had decreased significantly more in Group A compared with Group C (P < 0.05), but there were no other differences. After training, VAS-QLV scores in Group A had decreased significantly more compared with Group B and C (P < 0.05). In terms of acceptance, the VAS-A score was 7.6 ± 2.2 in Group A and 3.1 ± 2.8 in Group B (P =0.004), The acceptance rate was 70% in group A and 10% in group B. there was no significant correlation between age and VAS-A in either group A or group B (P > 0.05). Conclusion This study strongly suggests that vestibular rehabilitation training should be performed in children with vertigo to improve symptoms. For children with RVC with UVD but normal balance function, a single VOR adaptation program can effectively improve vertigo symptoms, and given its simplicity, time-effectiveness, and excellent outcomes, it is associated with better acceptance in children compared to classic Cawthorne-Cooksey training.